ChemInform Abstract: Ligand‐Enabled Methylene C(sp3)—H Bond Activation with a Pd(II) Catalyst. Issue 17 (4th April 2013) - Wasa, Masayuki; Chan, Kelvin S. L.; Zhang, Xing‐Guo; He, Jian; Miura, Masanori; Yu, Jin‐Quan
Abstract Best results are obtained using 2‐isobutoxyquinoline as the ligand (no stereochemical assignments for most compounds).